2013
DOI: 10.1071/ah12151
|View full text |Cite
|
Sign up to set email alerts
|

The hidden cost of medical student education: an exploratory study

Abstract: Objective. To examine the hidden cost of medical education at the Sydney Medical School, for which the University of Sydney does not pay.Methods. All face-to-face teaching provided for students in the Sydney University Postgraduate Medical Program was listed under two headings: teaching by university employed staff; and teaching by other health providers not paid by the university. All teaching hours in 2010 were extracted from detailed timetables and categorised under these headings. Time spent in lecture pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They did identify that apart from staffing costs, other costs included administrative time, decreased productivity and procuring extra equipment for student training. In some disciplines, such as medicine, it is commented that the cost of practicums is not sustainable without the voluntary teaching contribution of clinicians (Oates & Goulston ). From the projects’ results, it can also be seen that small private practices express similar concerns over costs.…”
Section: Discussionmentioning
confidence: 99%
“…They did identify that apart from staffing costs, other costs included administrative time, decreased productivity and procuring extra equipment for student training. In some disciplines, such as medicine, it is commented that the cost of practicums is not sustainable without the voluntary teaching contribution of clinicians (Oates & Goulston ). From the projects’ results, it can also be seen that small private practices express similar concerns over costs.…”
Section: Discussionmentioning
confidence: 99%
“…The cost to the university was $56 250 and the cost of non-university-paid staff (mainly from the NSW Health Department) was $34 326 per student per year. 5,6 Considerable concern has been expressed in Australia and overseas that relatively little time is spent on education during the intern year, [7][8][9][10][11][12][13][14][15][16] and it has been suggested that the intern year should have a greater educational emphasis than service emphasis. 15 There are few estimates in the literature of the proportion of interns' time devoted to education.…”
Section: Discussionmentioning
confidence: 99%
“…There is another aspect of goodwill that the industry's growth is threatening. A large proportion of clinical teaching of medical students is done by senior medical clinicians whose teaching is usually added on to a demanding clinical load with in many universities little or no payment for teaching . As governments demand increasing efficiencies from the health care system (making participation in teaching even more stressful) and as student numbers continue to increase, the goodwill of such teachers is also at risk.…”
mentioning
confidence: 99%